Manajemen Radio Streaming Bahasa FM Situbondo dalam Menarik Minat Pendengar - Imam Syafi'i (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The information technology revolution has spawned a television whose presence pampers its viewers to not only imagine in enjoying television broadcast programs. At a glance it seems to have shifted the radio position of the broadcast. But in its development radio still exist with its own market share. Radio remains an alternative medium with the auditive nature of making listeners without having to leave their busy, working while enjoying radio broadcasts. This is what makes the field of radio business continues to grow. One of them is PT Radio Bahana Suara Asembagus modulating frequency (BHASA FM Situbondo). With the rise of the internet today, trying to develop online radio through internet broadcasting, web casting with a new dimension of strong positioning, the format used as a reference, with a sharp concept aiming for a progressive and potential audience. Technology development has always been a priority for BHASA FM. Not just beat drums prestige, but as a form of struggle to satisfy the listener and advertiser. One thing that is not less important is the courage of BHASA FM Situbondo to advance in a very tight global competition as an industry-oriented broadcasting that oriented to the increasingly challenging through the management of BHASA FM Situbondo radio streaming to the listeners interest.